IMPLEMENTASI GOOD CORPORATE GOVERNANCE (GCG) DALAM PERSPEKTIF ISLAM PADA LEMBAGA PENDIDIKAN PESANTREN (STUDI KASUS PESANTREN MAMBAUS SHOLIHIN SUCI, MANYAR, GRESIK) - Anggita Rahmah, Audhie Ardah; Aviana Ningrum, Siti Masluchah; Handini, Nur; Maulana, Satria Bagus; Kusumaningtias, Rohmawati; Kusumaningsih, Ambar (Ekonomi Islam, 2023)
The purpose of this research was to analyze the implementation of Good Corporate Governance (GCG) from an Islamic perspective in Islamic boarding schools, namely the Mambaus Sholihin Islamic Boarding School. The application of the five GCG principles to the Mambaus Sholihin Islamic Boarding School uses a legal basis that is guided by existing laws and is linked to the Al-Qur'an and Al-Hadith. This research uses a descriptive qualitative methodology that collects data through question and answer and face to face with informants. The results of the research show that the application of GCG principles in an Islamic perspective has been implemented very well, although in the future it still needs to be improved for the progress and development of Islamic boarding schools.